مساهمة القيادة الاستراتيجية في تحقيق الميزة التنافسية للمؤسسة - سهام, موفق (Recherches économiques et managériales, 2013)
تواجه المؤسسات اليوم في سعيها الدائم نحو البقاء والحفاظ على موقعها التنافسي العديد من التحديات التي تفرضها اوضاع بيئة الأعمال ،مما يحتم عليها ان تستجيب لتلك التحديات من خلال اعتماد اليات متجددة و كذا استراتيجيات تنطلق من تحليل نقاط قوتها وضعفها ، بالإضافة الى تحديدها للفرص والتهديدات التي تواجهها، استراتيجيات تتلائم مع متطلبات التعامل مع مستجدات المنافسة القائمة في بيئة الاعمال.     ومن هذا المنطلق تعد القيادة الاستراتيجية المسؤول الاول عن تحديد التوجه الاستراتيجي للمؤسسة الرامي لتحقيق الاهداف الاستراتيجية للمؤسسة، هذا الى جانب انها تمثل فئة مميزة من الاصول الفكرية المهمة داخل المؤسسة، المرتكز الاساسي في تدعيم توجهات المؤسسة نحو بلوغ النجاح والتقدم التنافسي وضمان التفوق والتميز من خلال ادامة ميزتها التنافسية، وفي هذا الصدد يسعى البحث الى تسليط الضوء على مساهمة القيادة الاستراتيجية في تحقيق الميزة التنافسية للمؤسسة. الكلمات المفتاحية : القيادة الإستراتيجية ،الميزة التنافسية ، ابعاد التنافس Search summary:           Enterprises today in constant pursuit to survive and maintain its competitive challenges posed by conditions of the business environment, which makes it necessary to respond to these challenges through innovative mechanisms and strategies based on analysis of strengths and weaknesses, as well as to identify opportunities and threats, strategies adapted to the requirements of dealing with new competition in the business environment. From this perspective as strategic command is responsible for setting the strategic direction of the Organization to achieve the strategic objectives of the Organization, as well as a distinct class of important intellectual assets within an organization, cornerstone in strengthening enterprise trends towards success and progress and ensure competitive excellence by sustaining competitive advantage, and in this regard the search seeks to shed light on the contribution of strategic leadership in achieving competitive advantage for your organization. Keywords : strategic leadership, competitive advantage, competitive dimensions